Aging viscoelastic properties of cement paste - Patil, Poornima (Kansas State University, 2023)
This work is focused on assessing the aging viscoelasticity of cement paste using nanoindentation. First, sources of uncertainty in nanoindentation experiments for cementitious materials are identified. Results from this study indicate that a “critical indentation depth” exists such that individual indentations shallower than the critical depth demonstrate greater variability for all measured properties than deeper indentations. Surface roughness and the polishing method profoundly influence measured properties. Second, feedback controlled statistical based nanoindentation creep and stress relaxation tests are performed on cementitious material and polycarbonate to characterize the viscoelastic properties. A closed form linear viscoelastic analytical solutions are derived based on the elastic-viscoelastic correspondence principle to study the creep and stress relaxation response. The viscoelastic properties obtained from testing hardened cement paste and standard polycarbonate indicate strong agreement between the measured and the fit data. Additionally, nanoindentation based stress relaxation test appears to provide more converged data compared to creep tests, hence the study proposes nanoindentation as an additional and efficient tool to characterize the stress relaxation of cementitious materials. Third, investigation of the effect of combined neutron–gamma irradiation on cement paste is conducted to understand the viscoelastic behaviour of irradiated concrete in nuclear safety structures. The reduced modulus, relaxation modulus, and creep compliance of irradiated and the control samples obtained from reference creep nanoindentation test at various locations are presented and explained in detail in this study. The results demonstrate a considerable drop in reduced modulus and relaxation modulus of irradiated samples and a significant increase in the creep compared to the control samples. Lastly in the present study, the aging viscoelastic response of cement paste is measured and modeled using time shift approach and solidification method. The hydration of the cement paste is arrested at different ages (6hr., 12hr., 1day, 2day, 3day, 7day and 28 day) using solvent exchange and freeze dry method. The results emphasize that the time shift approach appears to be promising model to predict the aging viscoelasticity of cement paste at later (after 3 days) ages and solidification theory can effectively predict the aging viscoelastic behavior at early (less than 3 days) ages.
Keywords: Viscoelasticity; Irradiation; Nanoindentation; Cement paste; Uncertainty; Correspondence principle